The Influence of the Quality of Financial Reports on Investment Efficiency with Litigation Risk as a Moderating Variable (Empirical Study of Manufacturing Companies in Bei 2018-2022) - Ayu Febrianggi (GoodWill Journal of Economics, Management, and Accounting, 2023)
This study aims to examine the effect of the independent variables: the quality of financial reports (X) on investment efficiency (Y) with litigation risk as a moderating variable (Z) in manufacturing companies listed on the Indonesia Stock Exchange. The research method used is a quantitative method with an explanatory research approach. The population in this study is 193 companies' financial report data from manufacturing companies listed on the IDX for 2018-2022. The data collection technique in this study used a purposive sampling technique and produced a sample of 39 manufacturing companies listed on the IDX for 5 years. Data analysis techniques were processed using IBM SPSS Statistics. The results of this research indicate that the financial report quality variable has no effect on investment efficiency. Meanwhile, the litigation risk variable is able to moderate the relationship between the quality of financial reports and investment efficiency.